2018
DOI: 10.3892/ol.2018.8143
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of the runt-related transcription factor�1 and�3 genes in the development of acute myeloid leukemia

Abstract: Abstract. The aim of the present study was to evaluate the mRNA expression level of the runt-related transcription factor 1 (RUNX1) and runt-related transcription factor 3 (RUNX3) genes in patients with acute myeloid leukemia (AML). The etiology of AML is not yet fully known, but certain genetic factors may contribute to its manifestation. The RUNX1 and RUNX3 genes have been demonstrated to serve a role in the transcription process. The group investigated in the present study included 43 patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…However, in this study, we did not nd any correlation between RUNX1 expression and FAB classi cation, OS, and PFS (P = 0.348, P = 0.804, P = 0.314, respectively). This is similar to KRYGIER A et al, who concluded that high expression of RUNX1 has no relation to FAB classi cation of AML and mortality [47]. Our study found no associations between age, TLC, Hb, PLT, peripheral and bone marrow blasts and different ELN genetic groups and the level of RUNX1 expression.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in this study, we did not nd any correlation between RUNX1 expression and FAB classi cation, OS, and PFS (P = 0.348, P = 0.804, P = 0.314, respectively). This is similar to KRYGIER A et al, who concluded that high expression of RUNX1 has no relation to FAB classi cation of AML and mortality [47]. Our study found no associations between age, TLC, Hb, PLT, peripheral and bone marrow blasts and different ELN genetic groups and the level of RUNX1 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we observed a signi cantly higher RUNX1 expression in male patients (p = 0.046). This result was in contrast to the ndings of KRYGIER A et al who reported in his study on 43 polish De Novo AML cases using RT qPCR analysis technique that RUNX1 signi cantly expressed in females [47]. This disagreement may be due the difference in sample size or could be due to racial difference.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…2 a). Moreover, using previously published data [ 26 ] in the same patient cohort, the connection between expression levels of CEBPA and c-MYC and RUNX1 and RUNX3 expression level was analyzed. CEBPA expression level was not significantly associated with either RUNX1 or RUNX3 expression level (r S =0.270, p=0.0875 and r S =0,013, p=0.9366, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Weng et al demonstrated that GM-CSF attenuates MYC-associated gene signatures in t (8;21) (RUNX1-ETO) leukemia cells, but not in control cells by restoring the expression of a subset of MYC-repressed targets (e.g. CEBPA) , which promote a myeloid differentiation and apoptosis [ 26 ]. MYC and RUNX1 with two other factors, SP1 and GATA2, form multi-protein transcription complex which activates expression of SET , encoding important oncoprotein for AML development.…”
Section: Discussionmentioning
confidence: 99%